Agriculture for development in Africa: Options and way forward - Anandajayasekeram, P. (2008)
This paper discusses the theme 'Agriculture and Development in Africa'. It was presented at one of the AU Fridays of the commission forums. It looks into the concept of agriculture and development versus agriculture for development; evidence on the grounds; reasons for poor performance; emerging challenges; recent optimism and options for moving forward. The first part - agriculture for development - outlines the different ways agriculture contributes to development, as an economic activity and leading sector for economic growth, as a livelihood, as a provider of environmental services, peace and stability as pre-conditions for sustainable growth and development, new technology, improved human capital, sustainable growth in physical and biological infrastructure, effective institutes, and enabling political environment. Other topics of discussion include emerging food and energy crisis, recent technological advances in bio-technology and ICT, climate change, trade, market liberalization and the emerging agri-food system, emerging diseases, growing need intersectoral linkages, changing expectations of science and technology and innovation, globalization of private agricultural research and innovation, greater concern for the environment, meeting commitments and targets, under investment in agriculture and agricultural research, emerging optimism, and way forward.